Results from the Lebanese 2022 report card on physical activity for children and youth - Patrick Abi Nader; Ruba Hadla; Lina Majed; Lama Mattar; Suzan Sayegh (Elsevier, 2023)
Background/Objective: The Lebanese Active Healthy Kids Work Group (LAHKWG) synthesized literature published on physical activity (PA) indicators among ages 5- to 17- year-olds, using a recommended harmonized process by the Active Healthy Kids Global Alliance (AHKGA), to explore Lebanon's performance since its previous report card publication. Methods: Peer reviewed literature, national surveys, and gray literature published since 2017, on 10 common AHKGA and two LAHKWG recommended indicators were examined. Common indicators included overall PA, organized sport and PA, active play, active transportation, community and environment, sedentary behaviors, physical fitness, family and peers, school, and government. LAHKWG recommended indicators were sleep and weight status. LAHKWG members reviewed 764 records, of which 28 were selected for full review. A grade was assigned for each indicator using AHKGA's grading rubric and established benchmarks on data from nationally representative samples for children and youth. Results: Data from one nationally representative sample were available for ages 13-17 years (i.e., no data <13 years). Five indicators received "Incomplete" (organized sport and PA; active Play; physical fitness; family and peers; community and environment); overall PA received a D-; active transportation and sleep received a D+; school and government received a D; sedentary behaviors received a C; and weight status received a B-. Conclusion: The LAHKWG strongly encourages stakeholders to take concrete actions towards prioritizing PA promotion at a national level especially in the education sector. Offering more quality PA opportunities for Lebanese children and youth will be beneficial for their physical and mental health in any context.